Animal-Themed Flash Card Media to Improves Speaking Skills in Indonesian Language Subject for Grade I Elementary School Students - Kesuma, Putu Nadya Putri; Maria Goreti Rini Kristiantari; Dewi Anzelina (Universitas Pendidikan Ganesha, 2025)
This research is motivated by the lack of learning media used to improve the speaking skills. This study aims to describe the design, analyze the feasibility of media, and determine the effectiveness of animal-themed flash card media. The research model used is ADDIE. Data collection used interview, observation, and questionnaire methods. The subjects involved in this study included two contect expert, on einstructional design expert, one media expert, one practicality expert, three individual test students, and nine small group test students. This study used quantitative descriptive analysis, qualitative descriptive analysis, and inferensial statistical analysis. This research result were as follow. (1) The results of the design of flash card media ini the form of print with animal themes developed with the ADDIE model, (2) The result of feasibility through expert tests and product trials show that animal-themed flash card media are feasible to use in learning, (3) The effectiveness result show that animal-themed flash card media are effective for use in grade I elementary school students. The implication of this research is that it can make learning more interesting so that it has a positive effect on learning outcomes, especially improving student’s speaking skills.